Antología della litteratura latina Per le scuole medie superiori - CARENA, Carlo (MONDADORI, 1970)
Contiene: ADRIANO; AGOSTINO; AMBROSIO; CIPRIANO; CLAUDIO; CURZIO; DAMASO; DONATO; FEDRO; DECIMO; GELLIO; HISTORIA AUGUSTA; LUCANO; MACROBIO; MANILIO; COMODIANO; LATANZIO; NEMESIANO; MINUCIO; PERSIO; PRUDENCIO; SERVIO; TIBERIO; SINFOSIO; TACITO; VALERIO; PORFIRIO